Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd007271.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late tracheostomy for critically ill patients

Abstract: Updated evidence is of low quality, and potential differences between early and late tracheostomy need to be better investigated by means of randomized controlled trials. At present there is no specific information about any subgroup or individual characteristics potentially associated with better outcomes with either early or late tracheostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 56 publications
1
38
1
1
Order By: Relevance
“…This may reflect a shift in practice towards the belief that earlier tracheostomy improves outcomes for critically ill patients, which has been well-established in adults (Gomes Silva et al, 2012) and has begun to gain acceptance in other pediatric populations, including trauma (Holscher et al, 2014) and burns (Palmieri, Jackson & Greenhalgh, 2002). However, even beyond this broader overall increase in tracheostomy, we found that children with CHD accounted for an increasing proportion of all tracheostomy admissions.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a shift in practice towards the belief that earlier tracheostomy improves outcomes for critically ill patients, which has been well-established in adults (Gomes Silva et al, 2012) and has begun to gain acceptance in other pediatric populations, including trauma (Holscher et al, 2014) and burns (Palmieri, Jackson & Greenhalgh, 2002). However, even beyond this broader overall increase in tracheostomy, we found that children with CHD accounted for an increasing proportion of all tracheostomy admissions.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend the readers to refer other published documents for detailed discussion on prevention of HAP/VAP. [264401442] The strategies for prevention of VAP relevant to local conditions are listed in Table 18. The group re-emphasized staff education programs by hospital infection control committee and the concerned infection control nurse on a weekly basis (2A).…”
Section: Other Issuesmentioning
confidence: 99%
“…[24,46,47] The epicenter of study has been on the timing of the intervention. For example, evidence from the recent SETPOINT trial found that early tracheostomy in ventilated intensive care stroke patients is feasible and safe, in addition to decreasing sedation requirements and lowering ICU mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, some patients require tracheostomy in order to facilitate weaning from mechanical ventilation, long-term airway protection, or a combination of the two. [24] As of yet, no studies have specifically identified the rate of tracheostomy in a general sampling of patients with severe ischemic strokes. While the clinimetric properties of various outcomes scales are criticized, [25] the rate of tracheostomy is a well-documented patient-centered outcome.…”
Section: Introductionmentioning
confidence: 99%